Estrategias didácticas para desarrollar las competencias del área de matemática en estudiantes de la Institución Educativa Inicial N° 454 Mi Casita del Saber Nauta 2025 - Taminchi Huayunga, Maria July (2025)
The main purpose of this research was to evaluate how teaching strategies influence the development of mathematical skills in five-year-old children at I.E.I. No. 454 "Mi Casita del Saber," located in the city of Nauta 2025. To this end, a quantitative, applied approach and quasi-experimental design with pre- and post tests were adopted, allowing for a comparison of the achievements of an experimental group (n = 26) and a control group (n = 26). The measurement instruments were validated observation rubrics that assessed two skills: problem solving involving quantity and shape, movement, and location. The results show that, before the intervention, both groups presented similar performance, with average scores in mathematical skills (GE = 9,39; SD = 0,764; CG = 8,94; SD = 0.790). After implementing the strategies, the experimental group achieved higher mean scores in mathematical skills (GE = 15.99 and SD = 0.740), while the control group did not show significant improvements (CG = 11,29 and SD = 0.817). Student's t-tests confirmed statistically significant differences (p < 0,001) in favor of the experimental group, thus corroborating the general hypothesis and its two specific hypotheses. It is concluded that the research demonstrates that the systematic use of active and contextualized teaching strategies significantly improves logical-mathematical thinking in early childhood.